Estratégias genéricas de Michael E. Porter: um comparativo entre o posicionamento estratégico do Hotel Alfa e o setor hoteleiro de Foz do Iguaçu, Pr - Nojima, Rafael Galvão (2017)
The success achieved by organizations may be related to the competitive strategies adopted by them, especially as far as markets with fierce competition are concerned. The tourism and hospitality sector is important to the Brazilian economy and, among the several touristic attractions in the state of Paraná, there is the city of Foz do Iguaçu, where about 26% of the state’s means of accommodation are concentrated. Thence, the present study aims at comparing the strategic positioning of Hotel Alfa in relation to the hospitality sector in the city of Foz do Iguaçu, PR, in light of Michael E. Porter’s generic strategies. Data collection was done by means of document research, application of questionnaires in hotels in Foz do Iguaçu, interviews with experts in the field of tourism and hospitality and an interview with the manager of Hotel Alfa. Through qualitative and quantitative analysis, three of Porter’s generic strategies were identified in the hotels that participated in this research. In the two-star category, the total cost leadership strategy stood out. In the three-star and four-star categories, the most largely adopted strategy was the differentiation one, and in the five-star category there was a preponderance of the differentiation and focus strategies. A type of hybrid strategy, with characteristics of more than one of Porter’s generic strategies, was also identified. Hotel Alfa predominantly presented the differentiation strategy, aiming at the quality of services offered and not neglecting cost control. The information collected from the hotels in the city and from Hotel Alfa are in line with the view of experts. It is a diverse market that has cost control and quality services as primary needs. Considering the competitiveness of the hospitality market in Foz do Iguaçu, the present study contributes to businessmen and competent agencies in the field in the sense that it provides them with a strategic view of the city’s hospitality market. The instruments of data collection used may serve as a means of self-analysis for the businesses which intend to review their current strategic positioning.